Local Partners’ Perspectives on Health Student Service-Learning Placements in Low- and Middle-Income Countries: A Pilot Qualitative Study with Partners from Vietnam and Timor-Leste - Crawford, Emma; Hill, Anne E; Caine, Anne-Maree; Hunter, Lucy; Mandrusiak, Allison; Dunwoodie, Ruth; Fagan, Amy; Quinlan, Teresa; Branjerdporn, Nataya; Anemaat, Lisa (International Journal of Practice-based Learning in Health and Social Care, 2020)
Service-learning programs can provide clinical assistance in low-resourced settings while providing students with intercultural learning opportunities in diverse health contexts; local partners’ perspectives on international service-learning (ISL) programs are integral to ethical, effective and sustainable university-community partnerships; yet the perspectives of local partners remain under-represented in research. Interpretive description methods guided data collection and thematic analysis of qualitative responses from written questionnaires. Four local partners from Vietnam and Timor-Leste responded to questionnaires in this pilot project. Three themes were identified regarding benefits, underpinning factors for program effectiveness, and a further three themes related to desired improvements. According to local partners, benefits of ISL include skill and knowledge exchange, enhanced assessment and intervention strategies, and increased service quality. Communication and relationships were seen as underpinning factors of effective partnerships. Areas for further improvement included drawing more strongly on local partner strengths and perspectives, further collaborative preparation for the placements, and more regular communication. These preliminary findings align with existing research regarding benefits to local partners. Modelling effective practices, formal training and meetings, and ongoing case discussions may be some useful methods for achieving knowledge and skill exchange in ISL.